2016
DOI: 10.1016/j.gene.2016.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Role of HIF-1α in the hypoxia inducible expression of the thiamine transporter, SLC19A3

Abstract: Ensuring continuous intracellular supply of thiamine is essential to maintain metabolism. Cellular homeostasis requires the function of the membrane bound thiamine transporters THTR1 and THTR2. In the absence of increased dietary intake of thiamine, varying intracellular levels to meet metabolic demands during pathophysiological stressors, such as hypoxia, requires adaptive regulatory mechanisms to increase thiamine transport capacity. Previous work has established the up-regulation of SLC19A3 (THTR2) gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Expression of SLC19A3 in cancerous cells has been shown to be both increased and decreased and further studies are needed to elucidate the role SLC19A3 plays in cancer cells [224,231]. SLC19A3, like other transporters that have been discussed in the review, is also regulated by HIF-1a [232]. This study showed that under hypoxic conditions the expression of SLC19A3 is induced, leading to higher import of thiamine and suggesting an adaptive role for SLC19A3 in hypoxic environments [232].…”
Section: Vitamin Transporters In Cancermentioning
confidence: 85%
“…Expression of SLC19A3 in cancerous cells has been shown to be both increased and decreased and further studies are needed to elucidate the role SLC19A3 plays in cancer cells [224,231]. SLC19A3, like other transporters that have been discussed in the review, is also regulated by HIF-1a [232]. This study showed that under hypoxic conditions the expression of SLC19A3 is induced, leading to higher import of thiamine and suggesting an adaptive role for SLC19A3 in hypoxic environments [232].…”
Section: Vitamin Transporters In Cancermentioning
confidence: 85%
“…To assess changes in protein expression and localization, primary astrocytes were harvested as whole cell lysates (WCL) or nuclear lysates for Western blot analysis as previously described [ 42 ]. WCL (50μg) and nuclear lysates (25μg) were resolved by electrophoresis on 12% SDS-PAGE gels and transferred to a polyvinylidene difluoride membrane.…”
Section: Methodsmentioning
confidence: 99%
“…HIF-1α also mediates SLC19A3 ′s adaptive up-regulation during hypoxia [ 13 ]. However, the regulatory pathways for the two thiamine homeostasis genes diverge in that TPK1 expression was found to be translationally enhanced, while HIF-1α directly transactivates SLC19A3 gene expression [ 21 ]. Our findings for the inhibitory effects of YC-1 on TPK1 expression may also provide further support for the translational regulation of TPK1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously established an increase in the expression of SLC19A2 and TPK1 in breast cancer tissue when compared to normal breast tissue [ 20 ]. Furthermore, HIF-1α directly transactivates the adaptive expression of SLC19A3 and enhances thiamine uptake during hypoxic stress [ 13 , 21 ]. Despite thiamine’s implicit requirement for cellular metabolism within hypoxic tumor microenvironments, how changes in thiamine homeostasis impact malignant progression remain unclear.…”
Section: Introductionmentioning
confidence: 99%